Coalescence of residual histotripsy cavitation nuclei using low-gain regions of the therapy beam during electronic focal steering. (12th November 2018) - Lundt, Jonathan; Hall, Timothy; Rao, Akshay; Fowlkes, J Brian; Cain, Charles; Lee, Fred; Xu, Zhen
Abstract: Following collapse of a histotripsy cloud, residual microbubbles may persist for seconds, distributed throughout the focus. Their presence can attenuate and scatter subsequent pulses, hindering treatment speed and homogeneity. Previous studies have demonstrated use of separate low-amplitude ( 1 MPa) pulses interleaved with histotripsy pulses to drive bubble coalescence (BC), significantly improving treatment speed without sacrificing homogeneity. We propose that by using electronic focal steering (EFS) to direct the therapy focus throughout specially-designed EFS sequences, it is possible to use low-gain regions of the therapy beam to accomplish BC during EFS without any additional acoustic sequence. First, to establish proof of principle for an isolated focus, a 50-foci EFS sequence was constructed with the first position isolated near the geometric focus and remaining positions distributed post-focally. EFS sequences were evaluated in tissue-mimicking phantoms with gas concentrations of 20% and 100% with respect to saturation. Results using an isolated focus demonstrated that at 20% gas concentration, 49 EFS pulses were sufficient to achieve BC in all samples for pulse repetition frequency (PRF) ⩽ 800 Hz and 84.1% ± 3.0% of samples at 5 kHz PRF. For phantoms prepared with 100% gas concentration, BC was achieved by 49 EFS pulses in 39.2% ± 4.7% of samples at 50 Hz PRF and 63.4% ± 15.3% of samples at 5 kHz. To show feasibility of using the EFS-BC method to ablate a large volume quickly, a 1000-foci EFS sequence covering a volume of approximately 27 ml was tested. Results indicate that the BC effect was similarly present. A treatment rate of 27 ± 6 ml min −1 was achieved, which is signficantly faster than standard histotripsy and ultrasound thermal ablation. This study demonstrates that histotripsy with EFS can achieve BC without employing a separate acoustic sequence which has the potential to accelerate large-volume ablation while minimizing energy deposition.